Disinflation in Spain : The Recent Experience - Sobczak, Nicolas (IMF Working Papers; Working Paper ;, 1998)
This paper investigates the causes of the recent disinflation in Spain. A standard Phillips curve model is used to disentangle the contributions of three possible shocks: an adverse demand shock that raises unemployment, a positive supply shock resulting from relative price adjustments or structural improvements in the labor market, and a credibility shock that lowers inflationary expectations. The main element underlying Spain's recent disinflation appears to be a fall in inflation expectations, thanks to the country's commitment to participate in Economic and Monetary Union from the start, and policy actions geared to that end.